Une Jeunesse Amoureuse - Caillat, François (France : Gougeon, Christophe, 2012)
The narrator recounts his amorous youth in Paris in the 1970s : a tale of headlong, head-over-heels initiation into love, an intimate story as well as the adventure of a generation. By interspersing the city’s neighbourhoods with fragments of letters, photos of young women, and music of the day, the film constructs an amorous geography of Paris : that of the author, who for fifteen years there experienced the discoveries and excesses of his youth. As a counterpoint, one or two super-8 pictures of journeys - the counter-culture in the United States, and later the military dictatorship in Chile - call to mind how that period was.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films